2021
DOI: 10.1101/2021.01.08.425825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artemisia annuaL. extracts inhibit thein vitroreplication of SARS-CoV-2 and two of its variants

Abstract: SARS-CoV-2 (Covid-19) globally has infected and killed millions of people. Besides remdesivir, there are no approved small molecule-based therapeutics. Here we show that extracts of the medicinal plant, Artemisia annua L., which produces the antimalarial drug artemisinin, prevents SARS-CoV-2 replication in vitro. We measured antiviral activity of dried leaf extracts of seven cultivars of A. annua sourced from four continents. Hot-water leaf extracts based on artemisinin, total flavonoids, or dry leaf mass show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…ART as the main component of A. annua (sweet wormwood) extract has not been studied in SARS-CoV-2. Nair et al reported an antiviral effect in Vero E6 cells of artesiminin on SARS-CoV-2 with an EC 50 of 19.8 µg/ml ( 70 µM) (Nair et al, 2021). Studies suggest that artemisinin interferes with viral entry by interaction with the spike protein (Sehailia and Chemat, 2020), but it also affects postentry steps of infection (Cao et al, 2020b;Nair et al, 2021).…”
Section: Pharmacodynamic Effectsmentioning
confidence: 99%
“…ART as the main component of A. annua (sweet wormwood) extract has not been studied in SARS-CoV-2. Nair et al reported an antiviral effect in Vero E6 cells of artesiminin on SARS-CoV-2 with an EC 50 of 19.8 µg/ml ( 70 µM) (Nair et al, 2021). Studies suggest that artemisinin interferes with viral entry by interaction with the spike protein (Sehailia and Chemat, 2020), but it also affects postentry steps of infection (Cao et al, 2020b;Nair et al, 2021).…”
Section: Pharmacodynamic Effectsmentioning
confidence: 99%
“…[17] Other groups reported similar findings concerning pure synthetic artemisinin derivatives [25] and whole A. annua plant material. [18] Reports that teas made from A. annua and A. afra plants, [19] as well as Covid-Organics, a drink made from A. annua leaves and Ravensara aromatica in Madagascar, [20] have been used throughout Africa. Our earlier observation that A. annua extracts can inhibit SARS-CoV-2 in vitro prompted us to test whether such extracts can indeed inhibit coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pure, semi-synthetic substances, Artemisia teas and plant material have been explored for use to treat different diseases. [14] A. annua extract had shown anti-viral activity in vitro against SARS-CoV in 2005 [15] and SARS-CoV-2 (EC50 value: 2.5 µg/mL) [16] [18]. Standardized A. annua extracts with high artemisinin content are currently being studied in an ongoing phase 2 clinical trial against COVID- 19 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Effective and approved small molecule-based therapeutics are still lacking. Recently, we showed that hot-water extracts of dried leaves of seven cultivars of the medicinal plant, Artemisia annua L., used for millennia to treat malaria fever (Hsu, 2006) and sourced from four continents, prevented SARS-CoV-2 replication in vitro (Nair et al, 2021). Recently, anti-SARS-CoV-2 efficacy of A. annua extracts was independently confirmed (Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 98%